2020 Joint International Conference on Digital Arts, Media and Technology With ECTI Northern Section Conference on Electrical, 2020
DOI: 10.1109/ectidamtncon48261.2020.9090695
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Smart Agriculture Literacy of Farmers in Thailand

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Some studies observed a relationship between Smart Farming Adoption and some critical variables: Firstly is the perception of economic and commercial barriers (Caffaro & Cavallo, 2019. Secondly is the farmers' education in technology (Pivoto et al, 2019;Suebsombut et al, 2020). Thirdly is smart technologies' perception of use and the potential for radical changes in farm management [6], [17].…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…Some studies observed a relationship between Smart Farming Adoption and some critical variables: Firstly is the perception of economic and commercial barriers (Caffaro & Cavallo, 2019. Secondly is the farmers' education in technology (Pivoto et al, 2019;Suebsombut et al, 2020). Thirdly is smart technologies' perception of use and the potential for radical changes in farm management [6], [17].…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…As those papers are technologyoriented, they focus exclusively on providing a technical overview of the domain and/or tracking the most recent advancements in a field, giving little to no awareness to nonspecialists on technology integration guidelines. Other general survey papers focused on identifying trends and patterns of research on SF [45][46][47] or highlighting the role of different technologies in the agricultural industry in a particular region [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…The findings confirmed that Asian farmers are interested in technological devices. Meanwhile, a survey of smart agriculture literacy in aspect of farmers' experience and skills specific to Chiang Mai and Khon Kaen provinces in Thailand [7] revealed that farmers in Chiang Mai and Khon Kaen provinces have vastly different levels of smart agriculture literacy. As a result, the training section should take the participants' backgrounds into account.…”
Section: Introduction (Heading 1)mentioning
confidence: 99%